ANALYSIS OF DISCOUNT, FREE SHIPPING, AND PRODUCT DIVERSITY ON PRODUCT PURCHASE DECISIONS ON THE SHOPEE MARKETPLACE - Br Tarigan, Ema Septiani; Anisa Silvani; Br Tarigan, Jihan Syahreni; Hutagaol, Jarungjung (SEAN Institute, 2022)
The object of this research is the community around Jl.bunga kemuning No.1 LK-II Medan, Medan Tuntungan sub-district who conducts Marketplace Shopee, the purpose of this research is to find out discounts, free fees, product diversity partially and simultaneously influence product purchasing decisions on the market. Place Shopee. ApproachThe research used is quantitative, with associative data analysis techniques. The results of the study show discount positive and significant impact on product purchase decisions on the Shopee Marketplace. Due to the results of tcount (3.085) > ttable (1.993) with a significant value of 0.003 <0.05, H0 is rejected and Ha is accepted, free shipping has a positive and significant impact on product purchase decisions on the Shopee Marketplace. Due to the results of tcount (7.139) > ttable (1.993) with a significant value of 0.000 <0.05, H0 is rejected and Ha is accepted, the results of the statistical test of product diversity have a positive and significant impact on product purchasing decisions on the Shopee Marketplace. Due to the results of tcount (3.578) > ttable (1.993) with a significance value of 0.001 <0.05 then H0 is rejected and Ha is accepted. Tests carried out simultaneously show that the discount variable, free shipping and product diversity have an impact on product purchase decisions on the Shopee Marketplace. Due to the results of Fcount (109.178) > Ftable (2.73) with a significance level of 0.000 below the value of 0.05, H0 is rejected and Ha is accepted. With an Adjusted R Square value of 0.812 or 81.2%, which means that there is an impact between discounts, free shipping and product diversity on purchasing decisions of 81.2%, while the remaining 18.8% are other variables not examined by this study. for example promotions, prices, services and other variables.